Evaluación de la viabilidad del uso de la borra de café para la remoción de colorantes sintéticos en el agua (2020)
The research focused on evaluating the feasibility of using coffee grounds (CG) for the removal of synthetic dyes in water. Initially, a bibliographic review was carried out on the biosorption of different types of dyes with the use of this residue, observing the generalities regarding the modifications, their respective characterizations and the operating variables that influenced the process. The main methodologies used in the characterization of this residue were also identified, being the point of zero charge (PZC), the scanning electron microscopy (SEM), the Brunauer-Emmett-Teller isotherms (BET) and the Fourier transform infrared spectroscopy (FTIR), techniques that provide information on the structure, morphology and composition of the CG and the modified CG. Finally, it was shown that the biosorption process depends not only on the affinity between the biosorbent and the biosorbate, but also on the pretreatment or the modifications that this biomass has. As well as the variables pH, initial dye concentration, biosorbent dose, contact time, particle size and temperature, which influence the biosorption capacity or the percentage of removal of synthetic dyes in the water.